2011
DOI: 10.1002/ptr.3665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Plant‐derived Essential Oils on Central Nervous System Function Using Discrete Shuttle‐type Conditioned Avoidance Response in Mice

Abstract: Although plant-derived essential oils (EOs) have been used to treat various mental disorders, their central nervous system (CNS) acting effects have not been clarified. The present study compared the effects of 20 kinds of EOs with the effects of already-known CNS acting drugs to examine whether the EOs exhibited CNS stimulant-like effects, CNS depressant-like effects, or neither. All agents were tested using a discrete shuttle-type conditioned avoidance task in mice. Essential oils of peppermint and chamomile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
2
25
1
1
Order By: Relevance
“…Inhalation of Alpinia zerumbet essential oil, which contains 1,8-cineole, had anxiolytic effects in mice [22]. The essential oils of eucalyptus were found to decrease the avoidance rate in mice without affecting their response on a discrete shuttle-type task, a type of conditioned avoidance task [23]. In agreement with previous findings in mice, our results indicate that 1,8-cineole may exert anxiolytic effects in humans.…”
Section: Discussionsupporting
confidence: 89%
“…Inhalation of Alpinia zerumbet essential oil, which contains 1,8-cineole, had anxiolytic effects in mice [22]. The essential oils of eucalyptus were found to decrease the avoidance rate in mice without affecting their response on a discrete shuttle-type task, a type of conditioned avoidance task [23]. In agreement with previous findings in mice, our results indicate that 1,8-cineole may exert anxiolytic effects in humans.…”
Section: Discussionsupporting
confidence: 89%
“…Kuribara et al [20] demonstrated that the discrete shuttle-type conditioned avoidance task in mice is useful for distinguishing CNS stimulants and CNS depressants; that is, CNS stimulants facilitate the avoidance response and CNS depressants suppress the avoidance response in mice performing this task. Using the discrete shuttle-type conditioned avoidance task in ddY mice, I have previously shown that EOs of peppermint and chamomile facilitate the avoidance response as well as CNS stimulants and that EOs of orange, cypress, grapefruit, eucalyptus and rose suppress the avoidance response as well as CNS depressants [26]. However, the results of some EOs in the study were disagree with the claims for their effects made by the previous studies [12,13,[15][16][17]19].…”
Section: Introductioncontrasting
confidence: 59%
“…Thus, EOs obtained from various kinds of plant species and their constituents could show CNS effects. This notion is supported by the previous studies including those from our laboratory that have shown that various kinds of EOs and their constituents produce a variety of behavioural and/or CNS effects after inhalation or peripheral administration.…”
Section: Introductionsupporting
confidence: 68%
“…The absence of apigenin in CHA is likely one of the reasons for the absence of a sedative effect on ambulation . a suppressive effect on the conditioned avoidance response and an anxiolytic effect in the conflict tests …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation